The generalisation of n-cutting sites splicing language of Yusof-Goode model - Nooradelena, Mohd Ruslim; Yuhani, Yusof; Mohd Sham, Mohamad; Mudaber, Mohammad Hassan (AIP Publishing, 2025)
Formal Language Theory is a framework that describes a splicing system. Enzymatic activities in a certain splicing system produced a set of languages named splicing languages. The languages can be classified as inert, limit or transient. In this paper, the deoxyribonucleic acid (DNA) recombinant process is presented via Yusof-Goode (Y-G) model. The rule in the system is chosen to be non-palindromic with palindromic crossing sites. Two lemmas are shown which finally brought to the establishment of a theorem. The characteristics of the rule are then detailed in two cases which concerns its left and right context, whether it is a different left-right context, or if it has a similar left-right context. The generalised n-cutting sites splicing languages is then proved in a theorem and found to be in limit and transient languages.